Manejo integrado de Metamasius hemipterus en el cultivo de palma aceitera (Elaeis guineensis Jacq) en el Ecuador. - Aspiazu Romero, Anlly Katherine (2023)
The present bibliographic research on the integrated management of the pest Metamasius hemipterus in the oil palm (Elaeis guineensis Jacq) crop in Ecuador. It is a crop of great economic importance in many parts of the world, however, the presence of Metamasius hemipterus in the palm causes significant damage. It is a pest that feeds on palm tissues and foliage, and can drastically reduce the productivity and profitability of the crop. Integrated management of Metamasius hemipterus in oil palm has become a key strategy to ensure sustainable production of this crop. Integrated Pest Management (IPM) is a holistic approach that combines different control methods to minimise the negative effects of pests on crop production while protecting human health and the environment. IPM includes the use of biological, cultural, physical and chemical control methods, as well as monitoring and tracking of pest populations. A detailed description of Metamasius hemipterus and its impact on oil palm cultivation is presented. Biological control is one of the main components of IPM. It consists of the release of natural enemies, such as predators, parasitoids and pathogens, to control pest populations. Cultural methods, such as crop rotation, weed control and selection of resistant varieties, can also be used to reduce pest incidence on the crop. Physical methods, such as traps and trapping devices, are also useful to monitor and reduce pest populations. Relevant aspects of the biology and ecology of the pest, as well as the damage caused in oil palm plantations by the implementation of integrated pest management strategies in the oil palm plantation, will be discussed. It is concluded that this strategy could be key to ensure the sustainability of the crop and to protect biodiversity. Furthermore, it is recommended that future research be conducted to evaluate the effectiveness of other integrated management strategies and to adapt existing strategies.